Effects of Soil and Water Conservation Structures on Selected Soil Physicochemical Properties: The Case of Ejersa Lafo District, Central Highlands of Ethiopia - Adugna Tolesa; Siraj Mammo; Eve Bohnett (Applied and Environmental Soil Science)
Land degradation in the form of soil erosion and fertility depletion is the major environmental problem in Ethiopia. However, to curb this problem, soil and water conservation (SWC) structures are commonly practiced in many rural parts of Ethiopia. This study was conducted to assess the effects of SWC structures on selected soil physicochemical properties in Ejersa Lafo district. For this study, two kebeles (peasant associations) were selected purposively from the district based on the severity of soil erosion and information on SWC practices. The research design employed in this study was systematic, randomized, complete block design. A total of 12 composite soil samples were collected from the depth of 0 to 20 cm at two subwatersheds, namely, Jamjam laga batu and Koriso Odo guba with SWC and without SWC structures at three landscape positions. All the soil samples were analyzed following the standard and recommended procedures. The effect of independent variables (SWC practices and landscape positions) on the dependent variables (soil properties) was statistically tested using the SPSS computer program 21. In this study, most of the selected soil physicochemical properties were affected by watershed management intervention (SWC) structures. Soil moisture content (SMC), clay, pH, electrical conductivity (EC), total N (TN), available (AP), available K (AK), and organic carbon (OC) were higher in the subwatershed treated with SWC structures (conserved), whereas bulk density, silt, and sand were higher in the subwatershed without SWC structures (nonconserved). Most of the selected soil chemical properties were significantly varied (p<0.05) between conserved and nonconserved farm land except EC. All the selected soil physicochemical properties did not show any significant variation (p<0.05) at landscape positions except sandy soil. The physicochemical soil properties of selected parameters were in good conditions in the conserved areas with higher N and OM and lower BD, indicating fertility of the soil compared with the nonconserved land. The implementation of SWC structures improved some of the physicochemical properties of soil, such as SMC, clay particle, pH, EC, total N, AP, AK, and OC in the study area. Furthermore, efforts are required to enhance community adoption towards soil and water conservation. Additionally, further research has to be carried out on socioeconomic aspects and impacts of the intervention on crop productivity for better understanding of the sustainable use of the land.